Hubungan Fungsi Pengorganisasian Kepala Ruangan Terhadap Tingkat Kepuasan Kerja Perawat Pelaksana - Verawati - -; Erwin - -; Riri - Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This study aimed to identify correlation between organizational function of chief of nurses and nurse practitioner’s satisfaction at Mina ward, Ibnu Sina’s Islamic Hospital. Correlational study with cross sectional design was used in this research. Researcher used total sampling technique with total number of respondent was 30. The instrument was questionnaire that had been tested for validity and reliability. Analysis data used fisher’s exact test showed a significant correlation between organizational function of chief of nurses and nurse’s satisfaction with p value 0.004 (p value <α)at Mina ward, Ibnu Sina’s Islamic Hospital in 2014. Based on this research, chief of nurses have to build a good communication to nurse practitioner that will increase a good relationship of working. Keywords : Functions organization and job satisfaction